Effect of Prebiotic and Probiotic Fish Feed on Physical, Chemical and Biological Quality of Feed - Pratama, M. Indra Wahyu; Martinah, Anik; Yuniarti, Ating (The Journal of Experimental Life Science, 2021)
The limitations of fish in digesting food depend on the presence of enzymes protease, amylase, and lipase that react with substrates in the digestive channel of fish. Supplementation methods can be performed to increase fish growth by adding prebiotics and probiotics to the feed. This study aims to determine the influence of the difference in the length of time fermented prebiotic feed (sweet potato extract) and probiotics (Bacillus megaterium) on the quality of feed. The results of the physical analysis of fish feed showed the color looks brown, fishy smell, texture, and general conditions of feed seemed completely normal. Chemical analysis showed that the proteins were best improved in B3 treatment, with the period of fermentation approximately 72 hours. Biological analysis suggests that the longer the fermentation time taken, the higher the abundance of bacteria obtained.Keywords: B. megaterium, chemistry and biology of fish feed, physical analysis, sweet potatoes (Ipomoea batatas L)